PENGARUH TERAPI MUROTAL AL-QURAN TERHADAP STRES PASIEN HIPERTENSI DI RUANG PENYAKIT DALAM RSUD WALED CIREBON - Sri Susilawat1i; Sri Nurcahyati; Ahmad Syaripudin (LPPM ITEKES Mahardika, 2019)
Hypertension or high blood is where the occurrence of disorders of the blood vessels that cause oxygen supply in the blood to be slow down to the body tissues that need. Symptoms of increased blood pressure are characterized by dizziness, neck muscle aches and breathing difficulties (Mansjoer, 2010). Symptoms of such hypertension cause discomfort and insecurity that responded to the individual as a threat, causing stress and become the trigger of the occurrence of essential hypertension. One effective distraction technique used to treat stress in patients is to use murottal Koranic therapy, because murottal therapy of the Qur'an is an act of distraction. This research is a kind of quantitative research with quassy experiment research design. The research design used is Pretest-Posttest, Non-Equivalent Control Group Design. Sample selection using Quota sampling method. There are 2 groups: the intervention group and the control group. The sample size is 44 respondents. The result of the research with independent t test statistic test showed that there was a significant difference of the average stress level of hypertensive patient in the intervention group and the control group.